A matter of size: Does habitat use depend on body size in Amazonian small-stream shrimp species?. Issue 1 (2nd January 2023) - da Silva, Elmo Pereira; Magnusson, William E.
ABSTRACT: Natural selection is a key driver of organism size and shape, so resource use often depends on individual size. Among populations and assemblages there is overwhelming evidence that size- or stage-specific effects on niche occur mainly in habitat and food dimensions. A 2019 study by E. P. Silva and others, "Habitat segregation among freshwater shrimp species in an Amazonian rainforest stream system, " showed that Amazonian small-stream shrimp species show only slight habitat segregation at the scale of 50 m stream reaches, but that study did not take into account possible effects of intraspecific and interspecific differences in body size on habitat selection. We investigated through nighttime observations if conspecific shrimp of different sizes overlap in habitat use and whether heterospecific individuals of similar sizes differ in habitat use. Generalized linear mixed models were used to test possible relationships between body size and habitat features, and multivariate linear analysis and latent-variable model-based ordination were used to test for intraspecific and interspecific differences in habitat use. Mean frequency of use of habitat features differed among shrimp of different sizes and species, but use of habitat components strongly overlapped. Interspecific habitat overlap was greater among small individuals than large individuals. Our results indicate that size is not a major driver of habitat segregation in shrimp populations and assemblages, although it provides evidence of subtle ontogenetic shifts in habitat use by conspecifics of different sizes as well as differences between individuals of different species with similar sizes.